A influência da envoltória no consumo energético em edifícios comerciais artificialmente climatizados na cidade de Vitória-ES - Bernabé, Ana Carolina Alves (2012)
The deployment of cities have motivated the proposition of building more and more vertical in order to meet the demands for urban densification. Over time, the vertical development was linked to new technologies that initially came to give to the architect more projectual freedom. However, the possibility of reproducing models referenced in a modern and international style, led some professionals to neglect the close relation between architecture and the environment that it is inserted, leaving to artificial systems the role of ensuring thermal comfort for the users. However, the new energy scenario brought a reflection of the high demand for energy consumption in buildings, resulting in discussions, studies and development of a new reality, based on the concepts of energy efficiency. It is within this perspective that the research falls. The goal is to identify how and how much some strategies applicable to architectural envelope and inserted in the climate context of Vitória-ES, can influence the energy consumption of commercial buildings verticalized and artificially conditioned. The methodology proposed 108 models parameterized matching values for five investigated variables, they are: orientation, window wall ratio, solar factor, the existence of sun protection and absorptance of the opaque surface. These buildings were modeled after a reference building, so all other variables were controlled. As output data for the simulations we have established the final energy consumption. The analysis of these results was established in two ways. The first included the classification of the models that have achieved the level of efficiency through the procedure established by RTQ-C. The second involves the analysis of general and individual influence of each variable, and the potential for increase and reduction of energy expenditure of each one. As a result, it was found that changing the variables investigated led to a reduction of up to 27.88% in final consumption for the proposed model. The investigative tests suggest an even greater potential savings face to the most appropriate use of louvers and indicate the importance of lighting control in some cases.